Effects of dietary vitamin E on antioxidant defence mechanisms of juvenile turbot (Scophthalmus maximus L.), halibut (Hippoglossus hippoglossus L.) and sea bream (Sparus aurata L.) - Tocher, Douglas R; Mourente, Gabriel; Van der Eecken, Anne; Evjemo, Jan Ove; Diaz, Esther; Bell, J Gordon; Geurden, I; Lavens, P; Olsen, Yngvar (Aquaculture Nutrition, 2002)
In order to enhance growth, survival and quality during early juvenile stages of marine fish it is important to avoid lipid oxidation problems that are known to cause pathologies and disease. The aim of the present study was to characterise and compare the antioxidant systems in juvenile marine fish of commercial importance in European aquaculture, namely turbot (Scophthalmus maximus), halibut (Hippoglossus hippoglossus) and gilthead sea bream (Sparus aurata). The experiment investigated the interaction of the dietary antioxidant micronutrient, vitamin E, with antioxidant defence systems. Fish were fed diets of identical unsaturation index supplemented with graded amounts of vitamin E. The relationships between dietary and subsequent tissue vitamin E levels were determined as well as the effects of vitamin E supplementation on lipid and fatty acid compositions of both liver and whole fish, on the activities of the liver antioxidant defence enzymes, and on the levels of liver and whole body lipid peroxidation products, malondialdehyde (thiobarbituric acid reactive substances, TBARS) and isoprostanes. Growth and survival was only significantly affected in sea bream where feeding the diet with the lowest vitamin E resulted in decreased survival and growth. A gradation was observed in tissue vitamin E and PUFA/vitamin E levels in response to dietary vitamin E levels in all species. The activities of the main radical scavenging enzymes in the liver, catalase, superoxide dismutase and glutathione peroxidase generally reflected dietary and tissue vitamin E levels being highest in fish fed the lowest level of vitamin E. The indicators of lipid peroxidation gave consistent results in all three species, generally being highest in fish fed the unsupplemented diet and generally lowest in fish fed the diet with highest vitamin E. In this respect, isoprostane levels generally paralleled TBARS levels supporting their value as indicators of oxidative stress in fish. Overall the relationships observed were logical in that ...